QIRA’AT DALAM AL QUR’AN - Nasir, Abu (Asosiasi Dosen PTKIS Indonesia, 2024)
The Quran is an Arabic holy book. In its history, the Companions differed in reading or reciting it. The difference in qira'at is what, in turn, can affect the meaning and istinbath the law it contains. Qiraat in the Quran is one of the discussions, even becoming a science in itself. To make it easier for people to read and memorize the Qur'an, the Prophet Muhammad (Saw) gave the Companions the freedom to read the Qur'an in several dialects according to Jibril's teachings. As a result, different variants of recitation spread among the Companions. They spread throughout Islam to teach the Qur'ān to the people. They taught the Qur'ān according to the qira'at they received from the Prophet. Until the time of Umar bin alKhatab there was a disagreement in the process of inheriting the qiraat from the Prophet to some Companions. At that time, the Companions were well aware of the reasons for the difference of opinion and it did not have a bad impact on society, because it was based on the permission of the Prophet to facilitate the Companions in reading and memorizing. However, during the time of Caliph Uthman, sharp disputes began to emerge among the Companions, to the point that the qira'at of one school and the qira'at of another school blamed each other. The scope of the discussion of this paper revolves around the definition of qira'at, the origin and development of qira'at, the various qira'at and their criteria of validity, and the variations of texts and readings as well as the application in the interpretation of the Qur'an.